Determinants of Delegation of Duties and Responsibilities in the Administration of Secondary Schools in Mbeere South Sub-County, Embu County, Kenya 1 - Aceke, Masaku Flora; Muola, James Matee; Kimiti, R Peter (Stratford Peer Reviewed Journals and Book Publishing, 2019)
Delegation of tasks to the subordinates is an important activity in the administration of schools. It helps the principal in running the institution effectively though it may affect the subordinates negatively depending on how the process is done. The purpose of this study was to investigate on the determinants of delegation of duties and responsibilities in the administration of secondary schools in Mbeere South Sub-county, Embu County, Kenya. The study was guided by specific objectives including the establishment of the effects of training, attitude, incentives and workload on delegation of duties in the administration of secondary schools. The study confined itself to all secondary schools in Mbeere South Sub-county. The study adopted a descriptive research design. The study targeted 35 principals, 35 deputy principals and 315 assistant teachers. The study used questionnaires as the tool to collect data. Before the actual collection of data was done, a pilot test was carried out, where a sample of 10% of the targeted population was used. This was to ascertain the validity and reliability of the data collection instruments. Once the data was collected, it was analyzed by the use of Statistical Package for Social Sciences (SPSS) computer software. The analyzed data was presented using tables, charts and inferential statistics values. Based on the analysis and interpretation, it was found that training of employees on delegation gives the employees the knowledge of conducting the exercise. Further, it was found that attitude; incentives and workload affect delegation of duties and responsibilities in the administration of schools. In this regard then it is recommended to extend the same study to other counties and a comparison of the findings be done.
Keywords: Training; Attitude; Incentives; Administration of Secondary Schools & Embu County.; Workload